MODIFIKASI DESAIN TRAKTOR TANGAN â€œTEMBESIâ€ (STUDI KASUS DI PERKEBUNAN â€œTEMBESIâ€) - Supono, Agus; Ryadin, Agus Umar; Minta, Fadhlem Bassar (SIGMA TEKNIKA, 2019)
"Tembesi" hand tractor is a tool in the field of agriculture that is used to loosen the soil that is driven by gasoline fuel motor with a driving motor power of 6.5 Hp. From the results of the previous design testing (Rev_00) found a problem, where the tractor is difficult to move and when the rotating blade is then given a load the blade stops rotating. This study aims to improve the design of the "Tembesi" hand tractor which is focused on reducing the number of blade turns to increase the moment value and repair the part of the tractor wheel.From the design modification results, the blade rotation speed is modified from 1333 rpm to 450 rpm. From the plan moment value 6,925 kg.mm, the force produced by the "Tembesi" hand tractor blade is 387,79 Newton. Wheel modification is carried out using a 12-inch diameter (304.8 mm) rubber tire wheel.